Studies on wear resistance of the radial bearing design taking into account rheological properties of micropolar lubricant - M. A. Mukutadze; H. N. Abdulrahman; V. E. Shvedova; G. A. Badakhov; N. V. Zinoviev (Омский научный вестник)
The article is devoted to the development and analysis of a model of the motion of a micropolar lubricant in the working gap of a radial plain bearing with a fluoroplastic-containing antifriction composite polymer coating and with a groove on the supporting surface. New models are obtained on the basis of classical equations in the «thin layer» approximation and the continuity equation, which describes the turbulent mode of motion of a lubricant with micropolar rheological properties. The results of the numerical analysis of the obtained models of existing operational characteristics made it possible to obtain a quantitative assessment of the effectiveness of the support profile with a fluoroplastic-containing antifriction composite polymer coating with an axial groove. To complete the complex of studies and verify theoretical developments, experimental studies are carried out. The novelty of the work lies in the concretization of the technique of engineering calculations for the design of an effective radial bearing with an antifriction polymer coating with an axial groove on the bearing surface of the bearing bush, taking into account the dependence of the rheological properties of a micropolar lubricant on pressure and temperature in a turbulent mode, which makes it possible to estimate the value of the main operational characteristics: hydrodynamic pressure, load ability and coefficient of friction, as well as to expand the scope of practical application of models for engineering calculations. Thus, the design of a radial bearing with a polymer-coated support profile, a groove 3 mm wide, ensured a stable ascent of the shaft on a hydrodynamic wedge, which experimentally confirmed the correctness of the results of theoretical studies of a radial bearing with a diameter of 40 mm at a sliding speed of 0,32–3 m/s, load 4,9–24,5 MPa.